Analysing the usage and evidencing the importance of fast chargers for the adoption of battery electric vehicles. (September 2017) - Neaimeh, Myriam; Salisbury, Shawn D.; Hill, Graeme A.; Blythe, Philip T.; Scoffield, Don R.; Francfort, James E.
Abstract: An appropriate charging infrastructure is one of the key aspects needed to support the mass adoption of battery electric vehicles (BEVs), and it is suggested that publically available fast chargers could play a key role in this infrastructure. As fast charging is a relatively new technology, very little research is conducted on the topic using real world datasets, and it is of utmost importance to measure actual usage of this technology and provide evidence on its importance to properly inform infrastructure planning. 90, 000 fast charge events collected from the first large-scale roll-outs and evaluation projects of fast charging infrastructure in the UK and the US and 12, 700 driving days collected from 35 BEVs in the UK were analysed. Using multiple regression analysis, we examined the relationship between daily driving distance and standard and fast charging and demonstrated that fast chargers are more influential. Fast chargers enabled using BEVs on journeys above their single-charge range that would have been impractical using standard chargers. Fast chargers could help overcome perceived and actual range barriers, making BEVs more attractive to future users. At current BEV market share, there is a vital need for policy support to accelerate the development of fast charge networks. Highlights: Working with unique datasets of BEV and fast charge infrastructure usage in the UK and US. Typical energy transfer from fast chargers is approximately half of the BEV battery capacity. Regression model showed that fast charging is more influential than standard charging. Fast chargers could help overcome perceived and actual range barriers to BEV adoption. Without fast chargers, the transition from liquid-fuel vehicle to BEVs will be affected.